Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1074/jbc.ra120.013777
|View full text |Cite
|
Sign up to set email alerts
|

CaV channels reject signaling from a second CaM in eliciting Ca2+-dependent feedback regulation

Abstract: Calmodulin (CaM) regulation of voltage-gated calcium (CaV1-2) channels is a powerful Ca2+-feedback mechanism to adjust channel activity in response to Ca2+ influx. Despite progress in resolving mechanisms of CaM-CaV feedback, the stoichiometry of CaM interaction with CaV channels remains ambiguous. Functional studies that tethered CaM to CaV1.2 suggested that a single CaM sufficed for Ca2+ feedback. Yet, biochemical, FRET, and structural studies showed that multiple CaM molecules interact with distinct interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 93 publications
(174 reference statements)
0
3
0
Order By: Relevance
“…Several studies have emphasized the importance of CaM binding with the Ca v 1.2 IQ domain for regulating channel inactivation (CDI). It has been established that a single CaM prebound to the Ca v 1.2-IQ domain is necessary and sufficient to produce CDI of its associated channel ( 90 , 91 ). Mutations on CaM or IQ domain which weaken or abolish this interaction have been shown to affect CDI ( 65 , 91 , 92 , 93 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have emphasized the importance of CaM binding with the Ca v 1.2 IQ domain for regulating channel inactivation (CDI). It has been established that a single CaM prebound to the Ca v 1.2-IQ domain is necessary and sufficient to produce CDI of its associated channel ( 90 , 91 ). Mutations on CaM or IQ domain which weaken or abolish this interaction have been shown to affect CDI ( 65 , 91 , 92 , 93 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that a single CaM prebound to the Ca v 1.2-IQ domain is necessary and sufficient to produce CDI of its associated channel ( 90 , 91 ). Mutations on CaM or IQ domain which weaken or abolish this interaction have been shown to affect CDI ( 65 , 91 , 92 , 93 ). These data suggest a unique mechanism for E140G where the LQTS-associated variant can outcompete CaM-WT for binding to the C-terminal IQ domain of the channel, therefore preventing appropriate downstream regulation of Ca v 1.2 CDI through the NSCaTE domain.…”
Section: Discussionmentioning
confidence: 99%
“…At high [Ca 2+ ], 2 molecules of Ca 2+ /CaM bind to Cav1.2 channels [ 217 ]. Chakouri examined whether single or multiple CaMs are involved in Ca 2+ -dependent regulation of VGCCs using two CaM or Ca 2+ -insensitive CaM mutants (CaM 1234 ) tethered to the α and/or β subunit [ 218 ]. They found that VGCCs respond to signaling from the α-subunit-tethered CaM and concluded that Ca 2+ regulation depends on the pre-association of a single CaM with the α-subunit.…”
Section: Molecular Biological Studiesmentioning
confidence: 99%